KNOWLEDGE ,ATTITUDES AND PRACTICES OF HEALTH WORKERS ABOUT HEPATITIS B VACCINATION AT KASANGATI HEALTH CENTER IV WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Nyambura, Anna; Kansiime, David (Student's Journal of Health Research Africa, 2024)
Introduction Purpose The purpose of the study was to assess the Knowledge, Practice, and attitude of health workers about Hepatitis B Vaccination. Objective The study had three specific objectives; to determine the Knowledge of Hepatitis B vaccination among Health workers in Kasangati Health Center IV, To determine the Attitude towards Hepatitis B vaccination among Health workers in Kasangati Health Center IV, and to determine the Practice towards Hepatitis B vaccination among Health workers in Kasangati Health Center IV. Methodology The research was a cross-sectional study in which both qualitative and quantitative data were collected from a sample of 59 respondents who were obtained using a random sampling technique; the data collection method was a face-to-face interview using a questionnaire. Results The study findings showed that 86.6% of respondents had ever heard about Hepatitis B Vaccination. However, while some health workers demonstrated a good understanding of hepatitis B, there were gaps in knowledge among others. Furthermore, the study indicated that the majority (80%) of the study respondents were willing to receive Hepatitis B Vaccination. The study also revealed that 62% of the study respondents had received Hepatitis B Vaccination, 33% of the respondents. Conclusion The vaccination coverage among health workers was not optimal, with a significant proportion remaining unvaccinated. This gap in practice may be attributed to various factors, including the perceived risks of vaccination and potential side effects, as well as logistical challenges in accessing vaccination services within the healthcare facility. Recommendations Health workers should receive regular and comprehensive training on hepatitis B, its transmission, prevention, and the safety and efficacy of the vaccine.